Understanding the Necessity of Trauma-Informed Care in Community Schools: A Mixed-Methods Program Evaluation. Issue 2 (27th February 2019) - Báez, Johanna Creswell; Renshaw, Kristen J; Bachman, Lauren E M; Kim, David; Smith, Veronica D; Stafford, Rose E
Abstract: Community schools provide integrated services and supports, often through partnerships with community-based organizations, to mediate health and psychosocial barriers to learning faced by children from low-income families. Wediko Children's Services conducted a program evaluation with over 500 students at two schools in low-income communities in New York City to measure the impact of trauma-informed supports on students' social skills and problem behaviors. Wediko used a mixed-methods intervention explanatory sequential design with a pre- and posttest quantitative assessment using the Social Skills Improvement System Rating Scales (SSIS-RS) and a modified Adverse Childhood Experiences Questionnaire with qualitative data collection through student interviews after the intervention. The Wediko community school partnership was the intervention, with social workers providing assessments and tiered supports. The evaluation found that students reported lower social skills and higher problem behaviors as the level of reported traumatic experience increased. In addition, students with higher reported levels of trauma reported more problem behaviors over the course of a school year, in spite of receiving additional interventions. This article discusses the impact of trauma and community school supports on self-reported social skills and problem behaviors. It concludes with a discussion of the implications and recommendations for trauma-informed community school partnerships.